West Greenland caribou explosion: What happened? What about the future? - Cuyler, Christine (Rangifer, 2007)
In West Greenland, the 1993 caribou (Rangifer tarandus groenlandicus) population size estimate was 7000 to 9000 animals. Eight years later in 2001, the estimate was ca. 140 000. Relatively rapid rise and fall cycles of abundance in West Greenland caribou have been noted since the 1700s. Caribou have no natural predators in West Greenland. Combined with their high fertility and recruitment, this suggests that overabundance might be their greatest threat to stability. The 2005 population surveys indicate poor recruitment in two major populations and decreasing abundance in one. Given stocking densities are three to six-times the value considered sustainable, we expect strong competition between individuals for available food resources. Although the management goal is sustainable harvest of natural resources, if populations continue at their current size or increase further, there is a clear risk of range overgrazing and trampling. Unsustainable range use may result in density-dependent forage limitation with subsequent relatively rapid population decline over a series of years, e.g. a decade. As in the past, populations are expected to recover, and if true to the past, recovery will take the better part of a century. Furthermore, the role of catastrophic weather events may be of major importance. Abrupt collapse could be precipitated by a disastrous single year event, e.g. thaw-freeze icing or deep snow, because possibilities for dispersal to new ranges are limited. Regardless of management initiatives taken now, population declines or crashes may be inevitable for some West Greenland herds in the foreseeable future, but accurate predictions about herd trends are impossible. To understand the potential impact of future developments, Greenland caribou and their range must be studied within the wider context of climate change.